Few‐Layer Topological Insulator for All‐Optical Signal Processing Using the Nonlinear Kerr Effect. Issue 12 (16th September 2015) - Chen, Shuqing; Miao, Lili; Chen, Xing; Chen, Yu; Zhao, Chujun; Datta, Subhadeep; Li, Ying; Bao, Qiaoliang; Zhang, Han; Liu, Yong; Wen, Shuangchun; Fan, Dianyuan
Abstract : Topological insulators (TIs) are a new quantum phase of matter with topologically protected surface metallic states inside the insulating bulk states. Due to their unique single Dirac cone surface state, relatively low sheet resistance, and broadband optical operation, they have attracted enormous interests in both electronics and optics. Out of those above‐mentioned applications, electronic devices are seeking most attention until now. Here the experimental prototype for light processing device, TI‐coated microfiber (TCM), is demonstrated. Owing to the large Kerr coefficient of TI, TCM could operate as an effective optical Kerr switcher and broadband wavelength converter at the telecommunication band. This device could be well integrated with current high‐speed fiber optic communication networks and might well provide an approach for all‐optical signal processing through nonlinear processes. It is anticipated that few‐layer topological insulator might afford new opportunities for nonlinear photonic applications, especially in all‐optical routing, optical multiplication frequency, etc. Abstract : A suitable host nonlinear optical material is one of the most enticing promises for all‐optical signal processing. By combining a third‐order nonlinear optical material, topological insulator (TI), and microfiber, an all‐optical processing device is successfully prepared. This TI‐based prototype device can be used for optical Kerr switching and four‐wave‐mixing‐based wavelength conversion in the telecommunication band.